2011
DOI: 10.1002/mc.20758
|View full text |Cite
|
Sign up to set email alerts
|

Role of androgen receptor and associated lysine‐demethylase coregulators, LSD1 and JMJD2A, in localized and advanced human bladder cancer

Abstract: Bladder cancer is approximately three times more common in men as compared to women. We and others have previously investigated the contribution of androgens and the androgen receptor (AR) to bladder cancer. JMJD2A and LSD1 are recently discovered AR coregulator proteins that mediate AR-dependent transcription via recently described histone-lysine demethylation (KDM) mechanisms. We used immunohistochemistry to examine JMJD2A, LSD1 and AR expression in 72 radical cystectomy specimens, resulting in evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(170 citation statements)
references
References 54 publications
7
161
2
Order By: Relevance
“…12,[14][15][16][17][18][19][20] In accordance with our current findings in UUTUCs, significant decreases in the ARpositive rate have been reported in BCs, compared with nonneoplastic urothelial tissues. [14][15][16] In contrast, 2 other studies showed no AR expression in normal bladder urothelium. 18,20 In any of the studies involving UUTUCs, 10-12 AR staining was not performed simultaneously in normal/benign urothelial tissues.…”
Section: Discussionsupporting
confidence: 91%
“…12,[14][15][16][17][18][19][20] In accordance with our current findings in UUTUCs, significant decreases in the ARpositive rate have been reported in BCs, compared with nonneoplastic urothelial tissues. [14][15][16] In contrast, 2 other studies showed no AR expression in normal bladder urothelium. 18,20 In any of the studies involving UUTUCs, 10-12 AR staining was not performed simultaneously in normal/benign urothelial tissues.…”
Section: Discussionsupporting
confidence: 91%
“…UM-UC-3 cells were treated with CD24 siRNA and analyzed for differential growth with alamarBlue following treatment with R1881. Consistent with previous studies (25,27,28), R1881 induced the growth of control cells (Fig. 4A).…”
Section: Tumor Cd24 Expression Is Prognostic Of Outcomes In Bladder Csupporting
confidence: 93%
“…Previous studies have demonstrated that JMJD2A is widely overexpressed in human tissue and cell lines, including breast cancer (Li et al, 2011;Berry et al, 2012), colon cancer (Kim et al, 2012), bladder cancer (Kauffman et al, 2011), and prostate cancer (Shin et al, 2007), although there is rarely evidence about expression of JMJD2A in endometrial carcinoma. We determined JMJD2A expression level in 56 endometrial carcinoma tissues and 20 normal endometrial tissues by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, JMJD2A overexpression enhances estrogen-dependent transcription, and downregulation of JMJD2A reduces breast cancer cell growth by forming a complex with endogenous estrogen receptor (ER)α in vivo . In addition, JMJD2A overexpression enhances cell motility and invasion and metastasis of bladder and colon carcinoma cells (Kauffman et al, 2011;Kim et al, 2012). One study has shown that JMJD2A gene expression is upregulated in human prostate tumors, suggesting that JMJD2A may exert a tumor-promoting function (Cloos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%